Islamic compromise in the marriage of the Papuan Muslim Marind tribe - Faisal; Amri; Risman; Aisyah (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study was prompted by the traditional practice observed among the Marind tribe of Papua, speci;ically the custom of exchanging dowry during marriages, notably the "Wati Plant." Due to the plant's components inducing unconsciousness, the research aims to comprehend the nature of the Wati Plant and explore the rituals conducted by the Muslim community within the Marind Tribe during marriage traditions. Employing a ;ield research approach with an anthropological-theological perspective, the data collection involved interviews, observations, and documentation, subsequently analyzed using pertinent theories. The ;indings revealed that the Wati Plant has been part of the Marind tribe's heritage, initially considered a remedy for post-work fatigue by ancestral generations. This tradition persisted across generations. The study also unveiled the coexistence of Islamic and customary elements in Muslim Marind Tribe marriages, forming a harmonious compromise. This integration stems from a deep understanding of Islamic teachings and a commitment to honoring the Marind Tribe's ancestral customs.